Glândula de defesa do milípede Urostreptus atrobrunneus: estrutura e conteúdo - Sousa, Cristina Moreira de [UNESP] (2014)
Diplopods are animals intimately involved in ecosystem maintaining since they show a very significant contribution to the environment; revolve the ground during transportation, which leads to aeration of the same and improves the action of microorganisms, to the extent that assist in the microflora increase a through their feces and by feeding on decaying organic matter. These animals do not have large populations, but population explosions resulting from climate change, use of pesticides and other environmental imbalances. Have few predators due to the tough exoskeleton that make them unpalatable, and the presence of defensive glands that release substances of strong repulsive action. The defense strategies of millipedes can be classified into physical and chemical, which highlights the act of rolling up and defensive fluid, respectively. The millipede Urostreptus atrobrunneus have presented points of infestation in urban centers of the São Paulo state, Brazil, causing much disruption to the human population. Because it is a little-known species, conduct a study on the defense glands of these animals is interesting, since it has shown greater contact with human populations and other animals. Given the above, the objective of this study was: 1) Conduct a review of the millipedes defense mechanisms, comparing them with those found in arthropods and correlating the similarities observed between the groups. 2) Describe the morphology of the defense gland millipede U. atrobrunneus by histological, histochemical and ultrastructural techniques. 3) Analyze the volatile compounds present in the defensive secretion of the millipede by coupled mass spectrometry gas chromatography (GC- MS). The analysis allows to verify that the gland 's defense of U. atrobrunneus is of type 2, according to the classification proposed in the literature by Eisner et al. (1978) for glands defense diplopods; this gland is composed of a spherical glandular bag fitted...